Pengembangan Aplikasi Web Profile SMP Nusantara Anigou - Ignatius Gobai; Gunawan Prayitno (STMIK Pesat Nabire, 2024)
This community service project aims to develop a web-based school profile application for SMP Anigou Nabire. The application was designed to facilitate the dissemination of information about the school's profile to a wider community, including students, parents, and prospective students. The methods used in the development of this application include a needs analysis, system design, implementation, and testing. The result of this project is an application that can display essential information such as the school's history, vision and mission, organizational structure, facilities, extracurricular activities, and achievements. This application is expected to enhance the transparency and accessibility of school information and to support the school's promotion process to the community. The evaluation of the application shows that users are satisfied with the ease of access and completeness of the information provided. Further development is expected to include interactive features such as discussion forums and online registration.